2013
DOI: 10.1002/pc.22536
|View full text |Cite
|
Sign up to set email alerts
|

Bio‐inspired layer‐by‐layer assembled hybrid films for improvement of mechanical properties

Abstract: Inspired by many strong, toughness, and stiffness materials in nature, we first present bio‐inspired structure hybrid films fabricated by layer‐by‐layer assembly technique based on low‐surface‐energy graphite micro‐sheets and styrenic block copolymers. Compared with pure polymer films, the mechanical properties of the hybrid films have been greatly modified in failure stress, elastic modulus, and failure energy due to the rigid bio‐inspired structure. After graphite micro‐sheets surface modified by dopamine, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…, compared with the unmodified MMT, two strong absorbance peaks at 3612 and 1010 cm −1 were assigned to the stretching vibration of AlOH and SiOSi asymmetric stretching vibration, respectively . After the oxidative DOPA self‐polymerization, a new strong broad absorption band at 3429 cm −1 appeared in D‐MMT which can be attributed to catechol OH/NH groups stretching vibration in PDA molecules . Several characteristic absorption peaks at 1608, 1446, and 1281 cm −1 can be assigned to the overlap of CC vibrations in the aromatic ring and NH bending vibrations, NH shearing vibration, and CO stretching vibration of polyol on the polyphenol structure, respectively .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…, compared with the unmodified MMT, two strong absorbance peaks at 3612 and 1010 cm −1 were assigned to the stretching vibration of AlOH and SiOSi asymmetric stretching vibration, respectively . After the oxidative DOPA self‐polymerization, a new strong broad absorption band at 3429 cm −1 appeared in D‐MMT which can be attributed to catechol OH/NH groups stretching vibration in PDA molecules . Several characteristic absorption peaks at 1608, 1446, and 1281 cm −1 can be assigned to the overlap of CC vibrations in the aromatic ring and NH bending vibrations, NH shearing vibration, and CO stretching vibration of polyol on the polyphenol structure, respectively .…”
Section: Resultsmentioning
confidence: 98%
“…As a well‐known key component presenting in mussel adhesive proteins (MAPs), Dopamine (DOPA) could adhere to a variety of material surfaces based on the poly(dopamine) (PDA) self‐polymerization . It was found that PDA could be facilely coated on any type of solid surface, and the catechol groups in PDA can form the intricate interactions via hydrogen bonds, metal‐ligand complexes, and quinhydrone charge‐transfer complexes . Recent studies also demonstrated that, after the modification by PDA coating MMT, the thermomechanical properties, and compatibility of composites such as epoxy resin and styrene butadiene rubber have been significantly enhanced .…”
Section: Introductionmentioning
confidence: 99%
“…dopamine) is the first catecholamine synthesized from dihydroxyphenylalanine. In marine condition (an alkaline medium of pH 8.5) and in the presence of oxygen it is oxidized and selfpolymerized to a three dimensional cross-linked structure [18][19][20][21]. Due to its melanin-like structure it could prevent materials from surface corrosion and bulk degradation under strong acidic and alkaline conditions [22].…”
Section: Introductionmentioning
confidence: 99%
“…Important techniques for surface functionalizations are the layer-by-layer, grafting-to, and grafting-from methods. The classic layer-by-layer technique deposits oppositely charged polymer chains via electrostatic interactions onto the surfaces. , An important development in the layer-by-layer concept consisted of the substitution of the electrostatic interactions by covalent linkages, thus significantly increasing the stability. One key advantage of this method is the control of the individual layer sequence that is established orthogonally to the surface. Through the grafting methods, polymer chains are attached perpendicular to the surfaces either via addition of already synthesized (co-) polymers (grafting-to method) or via direct polymerization on the surface (grafting-from method) .…”
Section: Introductionmentioning
confidence: 99%